Peranan Kompetensi Digital Literacy Guru terhadap Motivasi Siswa Sekolah Dasar - Syahputra, Fadhlan Hartyas; Kurnianti, Endang M.; Hasanah, Uswatun (ANWARUL, 2024)
Low learning motivation and student learning outcomes cannot be separated from the influence of the learning process implemented. The application of technology based on teacher digital literacy competencies greatly influences student motivation. This research uses the Systematic Literature Review method or literature review. Several research results totaling twelve show that there is a significant impact of the use of technology in learning on student motivation. So it can be concluded that teacher digital literacy competency is very important in carrying out learning.